The Use Of Technology Techniques In The Formation Of Critical Thinking Of Schoolchildren As A Means Of Personal Self-Development (Eurasian Scientific Herald, 2024)
The article discusses the role of using interactive methods, as well as the introduction of critical thinking development technology in the classroom.